Beneficial effects of low-dose aspirin on aortic stiffness in hypertensive patients. (December 2014) - Pietri, Panagiota; Vlachopoulos, Charalambos; Terentes-Printzios, Dimitris; Xaplanteris, Panagiotis; Aznaouridis, Konstantinos; Petrocheilou, Katerina; Stefanadis, Christodoulos
While treatment with low-dose aspirin has been established as a therapeutic tool for secondary prevention, the role of aspirin on primary prevention remains controversial. Aortic stiffness and wave reflections are independent predictors of cardiovascular events. The aim of the present study was to investigate the effect of low-dose aspirin on aortic stiffness and wave reflections in hypertensive patients. We studied 30 patients with grade I hypertension. Fifteen patients were treated with 160 mg of aspirin and 15 patients with placebo. Aortic stiffness and wave reflections were assessed by measuring carotid–femoral pulse wave velocity (PWV) and heart rate-adjusted augmentation index (AIx75 ), respectively. All measurements were conducted at baseline and 2 weeks after treatment. In the aspirin group, there was a significant reduction in PWV compared to the placebo group (from 8.9±1.5 to 8.5±1.6 m/s for the aspirin group vs from 8.6±1.4 to 8.7±1.6 m/s for the placebo group, net change: –0.5 m/s; p =0.02). AIx75 showed a marginal decrease (from 28.0±5.4 to 26.2±5.0% for the aspirin group vs from 31.2±9.7 to 30.6±9.2% for the placebo group, net change: –1.2%; p =0.06). In conclusion, a 2-week course of aspirin administration has a favorable effect on aortic stiffness and, to a lesser extent, on wave reflections in hypertensive patients. Whether the reduction in arterial stiffness is translated to fewer cardiovascular events needs to be confirmed by future prospective studies.